Intra-Oral Spitz Naevus: A Case Report - Xavier, Ruth Lopes de Freitas (2008)
The Spitz nevus, also known as benign juvenile melanoma or a nevus of epitheloid and spindle cells, was first described by Sophie Spitz in 1948 and is most common in children and adolescents. They can present in three different ways: solitary nodular, multiple grouped, and multiple disseminated. The great majority of lesions are solitary, nodular, and are present in children and adolescents (57%–70%), with a slight preference for the female gender. The regions where they are most frequently found are the lower extremities, the head and neck, and the trunk. A Spitz nevus is usually pink, brown, or black in color. After an initial period of growth, the majority of Spitz nevi tend to stabilize their growth, reaching, in 95% of patients, a final size smaller than 6 mm.